Hyperthyroidism and bone mineral density: Dissecting the causal association with Mendelian randomization analysis. (28th September 2020) - Deshmukh, Harshal; Papageorgiou, Maria; Aye, Mo; England, James; Abdalla, Mohammed; Sathyapalan, Thozhukat
Abstract: Introduction: Untreated hyperthyroidism is associated with accelerated bone turnover, low bone mineral density (BMD) and increased susceptibility to fragility fractures. Although treatment appears to improve or even reverse some of these adverse skeletal effects, there is limited guidance on routine BMD assessment in hyperthyroid patients following treatment. By using Mendelian randomization (MR) analysis, we aimed to assess the causal association of hyperthyroid thyroid states with BMD and fractures using the UK Biobank. Methods: This MR analysis included data from 473 818 participants (women: 54% of the total sample, the median age of 58.0 years (IQR = 50‐63 years), median body mass index (BMI) of 26.70 (IQR + 24.11‐29.82 kg/m 2 ) as part of the UK Biobank study. The study outcomes were heel BMD assessed by quantitative ultrasound of the heel and self‐reported fractures. Beta‐weighted genetic risk score analysis was performed using 19 single nucleotide polymorphisms (SNPs) for Graves' disease, 9 SNPs for hyperthyroidism and 11 SNPs for autoimmune thyroiditis. Since the unadjusted risk score MR is equivalent to the inverse‐variance weighted method, the genetic risk score analysis was adjusted for age, gender and BMI. Sensitivity analyses were conducted using the Mendelian randomization‐Egger (MR‐Egger) and the inverse‐variance weighted estimate methods. Replication analysis was performed using the GEnetic Factors for Osteoporosis (GEFOS) consortium data. Results: MR analysis using beta‐weighted genetic risk score showed no association of genetic risk for Graves' disease (Beta = −0.01, P ‐value = .10), autoimmune thyroiditis (Beta = −0.006 P ‐value = .25) and hyperthyroidism (Beta = −0.009, P ‐value = .18) with heel ultrasound BMD. MR‐Egger and inverse‐variance MR methods in UK Biobank and GEFOS consortium confirmed these findings. The genetic risk for these hyperthyroid conditions was not associated with an increased risk of fractures. Conclusion: Our study shows that excess genetic risk for Graves' autoimmune thyroiditis and hyperthyroidism does not increase the risk for low BMD and is not associated fractures in the Caucasian population. Our findings do not support routine screening for osteoporosis following definitive treatment of hyperthyroid states.